Artykuły towarzyskie i brackie cechów krakowskich w perspektywie genologii lingwistycznej - rekonesans badawczy = Social and confraternity articles of Krakow guilds from the perspective of linguistic genology - research reconnaissance - Pałucka-Czerniak, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article was devoted to the analysis of the text and genre of the statute of urban professional communities called guilds with the example of social and confraternity articles of Krakow guilds from the 16th and 17th centuries. These articles, observed in pragmatic, structural, cognitive and linguistic-stylistic aspects, show the development of a specific genre, occurring mainly in the canonical and alternation variants. The indicated type of text is very cognitively interesting.
Keywords: statut; język; gatunek; artykuły brackie; artykuły towarzyskie; cechy krakowskie; statute; language; genre; confraternity articles; social articles; Krakow guilds